Pregnancy and pulmonary hypertension: a practical approach to management. (December 2013) - Kiely, David G; Condliffe, Robin; Wilson, Vicki J; Gandhi, Suarabh V; Elliot, Charlie A
Pulmonary hypertension remains a major cause of cardiac maternal death in the developed world. Over the last two decades, effective therapies for pulmonary hypertension have been developed, improving symptoms and survival. Consequently, increasing numbers of women with pulmonary hypertension and childbearing potential exist, with a number considering pregnancy. Patients with pulmonary hypertension may also present for the first time during pregnancy or shortly following delivery. The last decade has seen increasing reports of women with pulmonary hypertension surviving pregnancy using a variety of approaches but there is still a significant maternal mortality at between 12% and 33%. Current recommendations counsel that patients with known pulmonary hypertension should be strongly advised to avoid pregnancy with the provision of clear contraceptive advice and termination of pregnancy should be considered in its eventuality. In patients who are fully informed and who have been counselled regarding the risks of continuing with pregnancy, there is growing evidence that a multi-professional approach with expert care in pulmonary hypertension centres may improve outlook, although the mortality remains high.